Study on the value of serum miR-185-5p in assessing the degree of injury and prognosis of patients with traumatic brain injury - Wu, CaiHong; Chen, AiYu; Tong, Xiang; Tang, LiZhen; Lu, Tao (Journal of Medical Biochemistry, 2023)
Objective This study aims to explore whether serum miR-185-5p levels are related to the degree of injury and prognosis of traumatic brain injury patients. Methods Quantify the serum miR-185-5p level of 120 TBI patients. The Glasgow Coma Scale (GCS) was used to grade the damage, and the Glasgow Outcome Scale (GOS) was used to evaluate the prognosis 3 months after the trauma. Pearson correlation analysis was performed to determine the relationship between serum miR-185-5p level and injury degree and prognosis, and the value of serum miR-185-5p level on injury degree and prognosis was evaluated by receiver operating characteristic (ROC) curve. Results The level of serum miR-185-5p in patients with moderate or severe TBI was significantly higher than that in the mild group, and the level of miR-185-5p was closely related to the GCS score and GOS score. Serum miR-185-5p levels higher than 0.36 can distinguish TBI patients with mild and moderate injury with a sensitivity of 72.97% and a specificity of 97.62%; higher than 0.43, a sensitivity of 46.34% and a specificity of 91.89% can be distinguished significantly TBI patients are moderately and severely injured; higher than 0.36, with a sensitivity of 96.30% and a specificity of 60.24%, significantly distinguish the poor prognosis of TBI patients. Serum miR-185-5p level becomes an independent predictor of TBI patients with poor prognosis for 3 months. Under the ROC curve, the serum miR-185-5p level showed an effective ability to discriminate adverse outcomes at 3 months. Conclusions Serum miR-185-5p level is significantly correlated with the degree of injury and poor prognosis of TBI patients at 3 months, indicating that serum miR-185-5p level may be a biomarker that provides supplementary prognostic information to identify the risk of poor prognosis in TBI patients.